Measurements and Analysis of Secondary User Device Effects on Digital Television Receivers. (30th November 2009) - Newman, Timothy R.; DePardo, Daniel; Wyglinski, Alexander M.; Evans, Joseph B.; Rajbanshi, Rakesh; Petty, Victor R.; Datla, Dinesh; Weidling, Frederick; Kolodzy, Paul J.; Marcus, Michael J.; Minden, Gary J.; Roberts, James A.
Abstract : This article presents results from a study of the potential effects of secondary users operating in unoccupied television spectrum. Television spectrum is known within the wireless communications community as being underutilized, making it a prime candidate for dynamic spectrum access. The proposed use of this open spectrum has prompted questions concerning the quantity of available channel space that could be used without negative impact on consumers who view digital television broadcasts and the viability of secondary use of open channels immediately adjacent to a digital television broadcast channel. In this work, we investigate secondary device operation in the channels directly adjacent to a desired television channel, and the effects upon a selection of consumer digital television (DTV) receivers. Our observations strongly suggest that secondary users could operate "White Space Devices" (WSDs) in unoccupied channel bandwidth directly adjacent to a desired digital television (DTV) channel, with no observable adverse impact upon the reception of the desired channel content.